Pengembangan Sistem Pelaporan Kerusakan Jalan Otomatis Berbasis Sistem Embedded - Hanif Irfan Syah; Fajar Pradana; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The construction of road infrastructure is one program that is being activated by the Ministry of Public Works and Public Housing. Given the many benefits that can be felt by the community and government. But in addition to development, maintenance and repairs are also needed on the highway. Road damage can cause minor injuries to death. Decision making for repair and handling of road damage is often not on target, due to errors in determining priorities caused by the limitations of field officers. Besides that, the handling of road damage seems slow because the recapitulation of the data obtained still uses paper documents, which results in the handling of road damage being prolonged and road damage not being corrected immediately. In this study, a system developed using Raspberry PI microcomputer by applying the GPS sensor, vibration sensor and ultrasonic sensor implanted in motorized vehicles. This sensor will provide information regarding the level of road damage and the location of road damage with the help of the Google Maps API in real time to the relevant officers. So that decision making and handling repair of road damage can be done on target and immediately corrected.